On the excitation mechanism of erbium and ytterbium in the quaternary compounds InGaAsP - Wellmann, Peter; Winnacker, Albrecht; Pensl, Gerhard (Materials Research Society Symposium - Proceedings, 1996)
An efficient transfer of excitonic energy to rare earth (RE) ions is crucial for possible optoelectronic applications of RE doped semiconductors. In order to investigate the energy transfer mechanism to RE ions after optical above bandgap excitation we studied the intensity of the 4I13/2 →4 4I15/2-transition of Er3+ (1.54μm) and the one of the 2F5/2 →2 F7/2 -transition of Yb3+ (lμm) (loped into InGaAsP-layers lattice matched to InP. By varying the composition of the quaternary compoun ds, the bandgap energy together with the RE bound exciton energy were tuned relative to the RE excitation energy, and the effect on the RE luminescence intensity was observed. The results can be interpreted by stating a) that the energy transfer to the RE proceeds via the RE bound exciton, and b) that the intensity of the RE luminescence is essentially determined by the rate of back transfer of the RE excitation energy ERE to the bound exciton (with excitation energy Ebe). In this back transfer the energy of the excited RE ion plus the energy of 0, 1, 2 ... L0-phonons (energy Elo) is used to reexcite the bound exciton, instead of being emitted as an RE luminescence photon. For compositions where Ebe = ERE + n. Elo (n = 0, 1, 2...) we have a maximum of back transfer and correspondingly a, minimum in RE luminescence. In between the intensity has a, maximu